Effects of NiAl on precipitation behavior and mechanical properties of M2C strengthened secondary hardening steel - Yangxin Wang; Aijun Li; Tong wang; Junjie Sheng; Xin Cao; Chundong Hu; Han Dong (Journal of Materials Research and Technology)
A novel dual-precipitation steel was developed by introducing NiAl into secondary hardening ultrahigh strength steel. This steel exhibited a yield strength of 1.9 GPa, an ultimate tensile strength of 2.3 GPa, and an elongation of 9%. These exceptional mechanical properties can be primarily attributed to the synergistic strengthening effects of nanoscale NiAl and M2C dual-precipitates during the aging process. The influence of NiAl on the precipitation behavior of M2C and its precipitation strengthening effect were studied using atom probe tomography, transmission electron microscopy, and first-principles calculations. The results indicate that the precipitation of NiAl in the steel induces M2C nucleation around NiAl, preventing the coarsening behavior typically observed when M2C precipitates alone, where precipitates aggregate along dislocations. The high number density of NiAl increases the number density of M2C and reduces their size. Furthermore, at higher aging temperatures, the precipitation of NiAl in the steel inhibits the coarsening of M2C, thereby delaying the trend of strength reduction in the steel. Under the dual-precipitation strengthening effect of nanoscale NiAl and M2C, the yield strength of the steel can be increased by up to 1130 MPa, which is significantly surpassing the strengthening effect from the single precipitation of M2C during the aging process.